PENGARUH PENGGUNAAN MEDIA SOSIAL TIK TOK TERHADAP AKHLAK SISWA KELAS IX DI SEKOLAH MENENGAH PERTAMA NEGERI 2 PAMEKASAN TAHUN PELAJARAN 2023-2024 - Abdul Munib; Atnawi Atnawi; Nur Laila (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2023)
This research is motivated by the use of social media tiktok by students which often raises pros and cons in society. From this background, various kinds of influences will be known, especially on student morals, so that this can have an impact on the morals of the younger generation. The formulation of the problem in this research is; 1). Is there an effect of the use of TikTok social media on the morals of class IX students at Pamekasan 2 Public Junior High School?, 2). How Much Influence Does the Use of TikTok Social Media Have on the Morals of Class IX Students at Public Middle School 2 Pamekasan? The results of this study indicate that; 1). There is a significant influence between variable X on variable Y, this is based on data analysis with a significance level of P-value (0.04) < significance (0.05) then Ha is accepted and Ho is rejected. This means that variable X "influences" variable Y. 2). Tiktok social media has an effect on student morals by 0.145 or 14.5%, the remaining 85.5% is explained by other variables not included in this research model. The implication of this research activity is that there is an overview to researchers about the influence of social media (TIK TOK) on the formation of student morals. As education practitioners, at least you can benefit from the effects of social media so that they are used as material for in-depth study when carrying out educational activities, especially in forming the morals of students in general.